Stereotyped initiation of retinal waves by bipolar cells via presynaptic NMDA autoreceptors - Rong-wei Zhang (Nature Portfolio, 2016)
Retinal waves are important for visual system development. However, the mechanism involved in their generation remains largely unknown. Here using in vivotwo-photon imaging the authors identify the presence of retinal waves in zebrafish larvae and find that they are initiated at bipolar cells via presynaptic NMDARs.